Plato’s Crito on Civil Disobedience and Political Obligations - Kuniński, Tomasz (Peitho. Examina Antiqua, 2011)
The present paper focuses on the complex relation between ethics and politics in Plato’s Crito. While the issue is presented from a contemporary perspective, the problems of civil disobedience and political obligation are the present study’s primarily concern. The issue of civil disobedience concerns moral reasons for breaking the law, whereas the concept of political obligation refers to a moral duty to obey the law. When disagreeing with the view that Socrates in the dialogue argues for an unconditional obedience to the state, the article builds on the Apology. Subsequently, the similarities between the position of Socrates and that of H.D. Thoreau are investigated. Finally, the paper discusses the concept of political obligation so as to show that the argument in the Crito anticipates several modern theories. The modern controversies that this article covers are shown to play an important role in Plato’s dialogue, as they are the basis of Socrates’ political obligation.